Production technology development of millet at different ecological conditions - Seres, Emese; Sárvári, Mihály (Acta Agraria Debreceniensis, 2015)
The millet is a very special plant with good adaptation that gives the possibility for the late sowing and secondary production. However the effects of late sowing modifies the efficiency of the agrotechnological elements. The exainations – focused on this aspect – was conducted in the DU RINY and DU RIK in small plots in four replications in 2014. Among the examined factors (sowing time, nutrient supply, growing area) sowing time had the largest effect. The effectiveness of the agrotechnological elements decreases under unfavourable circumstances caused by the late sowing. The agrotechnical elements modifies the yields in the examined genotype. Sowing time had the biggest effect on the yields of millet. The genotype „Maxi” had the highest yield in the different treatment variations. The yield differences were significant between the sowing time and plant density variations, but the nutrient supply had not significant effect (the rate of precipitation was unfavourable in 2014 season).